Analisis Peran Audit Forensik dalam Mengungkap Penyimpangan dan Misleading Information pada Pengelolaan Dana Haji Indonesia Periode 2024-2026 - Nabilla Choiriya A; Desta Viananda; Nala Cahyani E; Tries Ellia Sandari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to explore the role of forensic auditing in uncovering indications of irregularities and misleading information in the management of hajj funds in Indonesia during the 2024–2026 period. Issues of transparency and accountability in hajj fund management have attracted public attention following audit findings and media reports indicating inefficiencies and potential inconsistencies in information disclosure. This research employs a qualitative approach using a case study method. The study utilizes secondary data, including audit reports from the Supreme Audit Agency of Indonesia, financial management reports from the Hajj Financial Management Agency, official publications from the Ministry of Religious Affairs of the Republic of Indonesia, as well as scientific literature and media reports. The findings reveal that forensic auditing plays a strategic role in identifying irregularities in fund management, particularly those related to weaknesses in internal control systems and potential inefficiencies. The study also identifies misleading information caused by information asymmetry between management institutions and the public, along with the delivery of information that is not fully comprehensive. From a qualitative perspective, this condition reflects gaps in governance and information communication that may influence public perception. This study emphasizes that forensic auditing functions not only as a tool for detecting irregularities but also as an instrument for improving transparency and accountability in public fund management. Therefore, strengthening internal control systems and improving the quality of information disclosure are necessary to minimize the risk of misleading information and increase public trust.